2007
DOI: 10.1016/j.jtcvs.2007.05.054
|View full text |Cite
|
Sign up to set email alerts
|

Survival outcomes after rescue extracorporeal cardiopulmonary resuscitation in pediatric patients with refractory cardiac arrest

Abstract: Objectives: We report our experience with extracorporeal cardiopulmonary resuscitation with extracorporeal membrane oxygenation in children having cardiac arrest refractory to conventional cardiopulmonary resuscitation and explore predictors for favorable outcome (survival with grossly intact neurologic status). Methods:We reviewed all patients who required extracorporeal cardiopulmonary resuscitation from 2000 to 2005. Multivariable regression analysis determined factors associated with favorable outcome and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
152
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(169 citation statements)
references
References 20 publications
13
152
4
Order By: Relevance
“…Our study supports a number of findings from an E-CPR study done in pediatric patients, which demonstrated that patient demographic factors such as age, weight and sex do not effect survival [6], and another paper indicating a correlation with duration of ECMO [16]. Our study also partially agrees with major conclusions from previous studies of adult E-CPR patients, which indicate that a state of acidosis is correlated with poor E-CPR outcomes [20].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study supports a number of findings from an E-CPR study done in pediatric patients, which demonstrated that patient demographic factors such as age, weight and sex do not effect survival [6], and another paper indicating a correlation with duration of ECMO [16]. Our study also partially agrees with major conclusions from previous studies of adult E-CPR patients, which indicate that a state of acidosis is correlated with poor E-CPR outcomes [20].…”
Section: Discussionsupporting
confidence: 91%
“…E-CPR provides a method to stabilize hemodynamics and provide end-organ perfusion when traditional CPR is inadequate and the cause of cardiac arrest is reversible. While many studies have assessed the efficacy of E-CPR in pediatric populations [5][6][7], fewer have investigated it in an adult population. The studies of adult populations have assessed the success of E-CPR in adult populations by mortality, and many have not taken end-organ function into account.…”
Section: Introductionmentioning
confidence: 99%
“…Additional efforts are targeted at correcting hematologic deficiencies, including maintaining the hemoglobin >10 mg/dL, platelet count >100 000 per 1 mm 3 , fibrinogen >200 mg/dL, and AT III >1 U/mL. 501 In an effort to limit contact activation during ECMO support, internal surface modifications have been made to ECMO materials. Among the most commonly used is covalently bonded heparin (Carmeda, Medtronic Cardiopulmonary, Anaheim, CA).…”
Section: Anticoagulation For Cardiac Ecmo In Children With Chdmentioning
confidence: 99%
“…This has been applied to all components of the circuit, including the internal tubing surfaces, cannulas, heat exchanger, and oxygenator. Alsoufi and colleagues 501 reported the outcome of 3 adult patients supported with a heparin-bonded ECMO circuit for postcardiotomy failure. All 3 patients were weaned from support, and 2 were long-term survivors.…”
Section: Anticoagulation For Cardiac Ecmo In Children With Chdmentioning
confidence: 99%
“…Survival for pediatric patients has been reported as anywhere from 23 to 73% based on published, single-center experiences [174][175][176][177][178][179][180][181][182]. Two multicenter registry database analyses have also been performed.…”
Section: Advances In Cerebral Resuscitation In Childrenmentioning
confidence: 99%